Assessment of age-based variations in physiological and anthropometric metrics in Kashmiri men - Haq, Mir Ahsan Ul; Tiwari, Sandhya; Tiwari, Sandeep (International Journal of Research in Medical Sciences, 2025)
Background: This study investigates age-related variations in physiological and anthropometric metrics among Kashmiri men aged 60-70 years, focusing on cardiovascular and body composition parameters across two age groups (60-65 and 66-70 years). Methods: Conducted under ethical approval from the university of Delhi, the study included 200 physically active participants, evenly divided into two age groups. Physiological metrics-systolic blood pressure (SBP), diastolic blood pressure (DBP), resting heart rate (RHR), body mass index (BMI), body fat percentage (BFP), waist-to-hip ratio (WHR), and basal metabolic rate (BMR)-were measured using validated tools. Data were analysed using descriptive statistics, independent t-tests, and Pearson’s correlation analysis, with significance set at p<0.05. Results: Significant differences were observed in RHR and BMR between the age groups. Participants aged 66-70 exhibited higher RHR (82.33±3.71 bm⁻¹) compared to those aged 60-65 (80.88±3.46 bm⁻¹, p=0.01). Conversely, the 60-65 group showed a higher BMR (1555.19±184.65 kcal/day) than the 66-70 group (1487.42±165.96 kcal/day, p=0.01). Non-significant differences were noted for SBP, DBP, BMI, BFP, and WHR, though BFP approached significance (p=0.06). Correlation analysis revealed strong interrelations among BMI, BFP, and BMR, with weaker associations between blood pressure metrics and WHR. Conclusions: Age-related changes in RHR and BMR highlight physiological adaptations among older Kashmiri men. These findings underscore the need for tailored health interventions addressing cardiovascular and metabolic risks in this demographic.